The Different of Protein Intake Between Chronic Renal Failure Patients with Malnutrition and Not Malnutrition in Hemodialysis Unit at dr. Abdul Moeloek Hospital Bandar Lampung - Dian Isti Angraini (JURNAL KEDOKTERAN DAN KESEHATAN, 2015)
Chronic renal failure patients undergoing hemodialysis are at risk of malnutrition, especially protein energy malnutrition. Adequate protein intake in hemodialysis patients aims to compensate for the loss of protein due to the hemodialysis process and to fullfill of basic physiological functions of the body. Malnutrition can increase the risk of morbidity and mortality. This study aims to determine the differences between the mean intake of protein in hemodialysis patients are malnourished and not malnourished. This study is an observational analytic with cross sectional design, in 43 patients with chronic renal failure undergoing hemodialysis in hemodialysis installation dr. H. Abdoel Moeloek in October to December 2013, taken with consecutive sampling technique. Malnutrition was the underweight status based on assessment of body mass index (BMI). Protein intake was obtained by the method of assessment of food consumption using semiquantitative food frequency questionnaire quesionaire (SQ-FFQ) that explores history of the patient ate during the last week. The results showed that subjects who were malnourished as much as 16.3%, and less protein intake was 36.5%. The mean intake of protein malnourished subjects (54 grams / day) lower than in subjects who are not malnourished (60.4 g / day). There were no differences between the mean protein intake was statistically significant between the groups malnourished and not malnourished (p = 0.163). Conclusion: there are no differences between the mean protein intake was statistically significant in subjects who are malnourished or not malnourished.